Modifikasi Polietilen sebagai komposit Plastik Polimer Biodegradable dengan Filler Tepung Kulit Pisang Talas - Rahmat Basuki; Ninis Hadi Haryanti; Suryajaya Suryajaya; Sadang Husain (Jurnal Fisika FLUX, 2021)
Synthetic polymer polyethylene LDPE has been grafted with natural polymers of banana talas (Musa paradisiacal Var sapientum L.) peels flour. The aim of this research is to make compossed plastic of the thermoplastic banana peels flour with LDPE resins plastic based on mechanic and degradation behaviours. Low Density Polyethylene (LDPE) resins, glycerol, banana peels, humus soil, xylene p.a as the raw materials. Thermoplastic banana peels flour produced by added 30% glycerol concentration and then by aging for 2 weeks. The mixing of the thermoplastic banana peels flour with LDPE resins using a ratio of 1:3, 2:3 and 3:3. Xylene (coupling agent) 6 times of the total mass were added to increase compatibility between thermoplastic banana peels flour and LDPE. The mechanical properties of composite were analyzed using ASTM D638 method and the biodegradation capability composite were charactherized using soil burial test method. The results show that tensile strength in the ratio of 1:3, 2:3, 3:3 respectively were 28.94 kg/cm2, 36.16 kg/cm2, 29.94 kg/cm2. The percentage of residual weight show the biodegradation capability in the ratio of 1:3, 2:3, 3:3 was 98.46%, 97.67%, 98.24%. Mixing ratio of 2:3 thermoplastic banana peels flour and LDPE has the best value of tensile strength and degradation capability. Mixing ratio of 2:3 thermoplastic banana peels flour and LDPE has the best value of tensile strength and degradation capability.